2019
DOI: 10.1088/1742-6596/1281/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrolyte composition on electrochemical formation and properties of ceramic-like coatings on aluminum alloys

Abstract: The electrochemical formation of ceramic-like coatings on D16 aluminum alloy was carried out using microarc oxidation method in phosphate (1.5 g/L NaOH + 9 g/L Na2SiO3 + 3 g/L Na3PO4) and molybdate (5 g/L NaOH + 30 g/L Na2SiO3 + 5 g/L (NH4)6Mo7O24) electrolytes. White and black ceramic-like coatings with thickness of 200–300 microns were obtained in phosphate and molybdate electrolytes, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…It was found that the use of different electrolytes leads to different surface porosities of the coatings, with better properties for the sodium phosphate electrolyte. Much attention is also paid to the influence of the electrolyte composition on the microarc oxidation process in many other works [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the use of different electrolytes leads to different surface porosities of the coatings, with better properties for the sodium phosphate electrolyte. Much attention is also paid to the influence of the electrolyte composition on the microarc oxidation process in many other works [41][42][43].…”
Section: Introductionmentioning
confidence: 99%